The influence of variation at the killer cell immunoglobulin-like receptor gene complex on human disease - Carrington, Mary (Henry Stewart Talks, 2009)
Introduction to KIR variation and disease association – Distinguishing KIR A and B haplotypes – Effect of KIR haplotype variation on pregnancy outcome – KIR association with risk of cancer and infectious diseases – Contrasting effects of KIR/HLA genotypes on viral infections vs. cancer
Updated at 2021/08/31